COVID-19 vaccine uptake among nursing officers: a cross-sectional study in a tertiary care hospital in Sri Lanka - Liyamini Karunaratne; Maheeka Seneviwickrama (College of Community Physicians of Sri Lanka, 2024)
Introduction: Vaccination against COVID-19 was considered an i mportant public health intervention to control the pandemic. However, the vaccine uptake was not satisfactory among Asian nurses and less explored in Sri Lankan setting. Objectives: To describe the compliance with the COVID-19 vacci ne among nurses in a tertiary care hospital in Sri Lanka with its associated factors Methods: This cross-sectional study was conducted in January 2022,  one year after the introduction of the COVID-19 vaccination to Sri Lanka. Stratified sampling method was used to select 415 nurses from District General Hospital Matara. Data collected using a pre-tested, self-administered questionnaire were summarized with descriptive statistics. Uptake of two primary doses and one booster dose was considered full compliance. The associations were evaluated with the Chi-squared test at p<0.05 significance level and adjusted f or confounders using multiple logistic regression. Results: With a 91.1% response rate (n=378), full compliance with  the COVID-19 vaccine was noted among 51.8% (n=196). There had been an active demand for the first dose among  84.7% which declined to 70.9% and 26.7% by the second and booster doses, respectively. Only 107 (28.3%) were willi ng to accept another dose if recommended in the future. The most influential reason for vaccine uptake as reported  by a majority was to prevent complications of COVID-19 disease. The most reported reason for reluctance was the  vaccine's inability to protect against new strains of the virus. Age, nursing qualifications, nursing grade and knowle dge on COVID-19 vaccine showed a significant association with vaccine uptake in bivariate analysis. However, onl y knowledge retained significant with vaccine uptake (adjusted odds ratio (aOR)=1.9; 95% CI=1.2, 2.9; p=0.003)  after adjusted for confounding effects using multiple logistic regression. Conclusions & Recommendations: There exists a gap in com pliance with COVID-19 vaccine among study participants. Targeted interventions should aim to empower and impr ove vaccine related knowledge among nurses in future vaccination programs.